Incidence and Socioeconomic Impact of Intestinal Parasitic Infections among School Going Children of Private and Public Sectors Schools - Zahid Ullah Khan, Salman Khan, Sajjad Khan, Khalida Kousar, Ahsan Saidal, Awal Meer, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Parasitic infection is one of the most common infections in school age children because of poor quality of water, deprived sanitation system and lack of enough health care facilities in underdeveloped countries. Parasitic infections lead to anemia, growth retardation, weight loss, and other physical and mental health problems in children. Current study is designed to evaluate frequency of different intestinal parasitic infections and possible associated risk factors among school students in of District Buner Pakistan. Material and method: This Descriptive cross-sectional study was conducted at Riaz Clinical Laboratory District Buner. All asymptomatic school going children between 5 to 15 years’ age of both genders were included in the study. Those students who had present with symptoms of gastrointestinal infection were excluded from the study. A total of 440 samples were collected from different public and private school’s children. Out of total 240 samples were collected from public sector schools and 200 samples from private sector school’s children. A pretested structured questionnaire was used to gather data on socio-demographic and associated risk factors. The adequate stool specimens were collected in sterile, screw caped disposable plastic container. All samples were examined under microscope using a direct wet mount and formal ether concentration technique. Data was analyzed through SPSS-22 and presented in the form of tables, Pie chart and bar graphs. Results: Out of 440 samples, 23.63% (104/440) were positive for an ova and cysts of different parasites. The parasite positivity ratio is greater in public sector school children (30%) compare to private sector school children (16%). Taenia saginata were most common parasite (8.4%) in school age children followed by Hymenolepis nana (5.68%), Ascaris lumbricoides (5.45%), Enterobius vermicularis 1.13%, and Strongyloides stecoralis (0.68%) were least common parasite in District Buner, Khyber Pukhtoonkhwa. Conclusion: Major contributor for the high prevalence of parasitic infections in public school children were found to be poor personal and environmental hygiene, lack of proper sanitation, contaminated food and water supply, personal habits of the children like nail biting and finger sucking, illiterate mother and low socio-economic status of the individuals. Keywords: Intestinal parasites, Worm infestation, School going children, Socioeconomic impact